KOMUNIKASI DALAM AL-QUR’AN DAN KAITANNYA DENGAN PENDIDIKAN - Asad Asad (Universitas Islam Negeri Sumatera Utara Medan, 2020)
Education and learning is a process never be separated from communication activities. It can be said, learning is a communication activity itself, because teaching is conveying subject matter by educators and recipients of material by students. This activity is communication. Accordance with the understanding of the communication namely; sending and receiving messages or news between two or more people, where messages are sent by the teacher and received by students. (Anton M. Mulyono, Editor